2002
DOI: 10.1093/treephys/22.2-3.129
|View full text |Cite
|
Sign up to set email alerts
|

Needle anatomy changes with increasing tree age in Douglas-fir

Abstract: Morphological differences between old-growth trees and saplings of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) may extend to differences in needle anatomy. We used microscopy with image analysis to compare and quantify anatomical parameters in cross sections of previous-year needles of old-growth Douglas-fir trees and saplings at the Wind River Canopy Crane site in Washington and at three sites in the Cascade Mountains of Oregon. We also compared needle anatomy across a chronosequence of 10-, 20-, 40- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 28 publications
9
44
0
1
Order By: Relevance
“…Quicker and earlier response in younger 1-year-old cuttings and higher rooting rates, are in agreement with several researches that indicate that capability for rooting is lost between 3 and 5 year old in gymnosperms [6] [10] [11] [25] [26]. Anatomical changes observed in both types of needles are in agreement with reports in Douglas-fir and P. halepensis [27] [28], indicating anatomical differences between young and old needles. Needles from younger trees presented a smaller vascular cylinder and increased mesophyll area.…”
Section: Discussionsupporting
confidence: 91%
“…Quicker and earlier response in younger 1-year-old cuttings and higher rooting rates, are in agreement with several researches that indicate that capability for rooting is lost between 3 and 5 year old in gymnosperms [6] [10] [11] [25] [26]. Anatomical changes observed in both types of needles are in agreement with reports in Douglas-fir and P. halepensis [27] [28], indicating anatomical differences between young and old needles. Needles from younger trees presented a smaller vascular cylinder and increased mesophyll area.…”
Section: Discussionsupporting
confidence: 91%
“…Leaf thickness and chlorophyll content appear to increase during the transition from the juvenile to adult phase in tree species (Greenwood, 1995;Greenwood et al, 1989;Poethig, 1990). These changes may increase the photosynthetic rate per leaf during the phase transition, resulting in higher assimilated productivity per tree in adult trees (Apple et al, 2002). In this study, leaf area and the SPAD value increased from A to F in Figure 2d and e, suggesting an increase in the photosynthetic rate per leaf.…”
Section: Discussionsupporting
confidence: 48%
“…Increasing stand age was associated with greater SLA, perhaps due to the effects of lower water potentials and greater water stress on the [1] found that needles in young saplings (∌10 years-old) were longer and had proportionately smaller vascular cylinders, larger resin canals and few hypodermal cells when compared to needles on mature trees (∌450 years-old). In addition, mean needle thickness was ∌9% lower when needles from 20 to 40 years-old trees were compared to mature trees [1]. Kennedy [18] found that specific leaf weight (1/SLA) in the upper canopy of Douglas-fir and lodgepole pine (Pinus contorta var.…”
Section: Discussionmentioning
confidence: 94%